Ideational Metafunction Analysis of Power Domination in Joko Widodo’s Job Creation Law Speech on October 9th 2020: A Critical Discourse Analysis - Cici Wahdania; Hamzah Hamzah (English Language and Literature, 2022)
This study aims to investigate the power domination strategy of Joko Widodo’s Job Creation Law speech on October 9th 2020. The current study utilizes Critical Discourse Analysis (CDA) model to unmask the power domination strategy through language use. The Ideational metafunctions of SFL is used in this research as the tool for analyzing the textual dimension and further investigation of discursive practice. The results prove the existence of power domination. From the interpretation or discursive practice analysis of the ideational metafunctions, the positioned of the participant clearly shown that there are power domination strategies of Joko Widodo in delivering his speech.